Energy economics CO₂ emissions in China - Wei, Yiming (Springer, 2011)
"Energy Economics: CO2 Emissions in China" presents a collection of the researches on China's CO2 emissions as studied by the Center for Energy & Environmental Policy Research (CEEP). Based on the analysis of factors related to global climate change and CO2 emissions, it discusses China's CO2 emissions originating from various sectors, diverse impact factors, as well as proposed policies for reducing carbon emissions. Featuring empirical research and policy analysis on focused and critical issues involving different stages of CO2 emissions in China, the book provides scientific supports for researchers and policy makers in dealing with global climate change.